Enhancing Phase Change Material Efficiency in Wavy Trapezoidal Cavities: A Numerical Investigation of Nanoparticle Additives - Ilias Benyahia; Aissa Abderrahmane; Yacine Khetib; Mashhour A. Alazwari; Obai Younis; Abdeldjalil Belazreg; Samir Laouedj (Physics)
Phase change materials (PCMs) are widely used in latent heat thermal energy storage systems (LHTESSs), but their low thermal conductivity limits performance. This study numerically investigates the enhancement of thermal efficiency in LHTESSs using nano-enhanced PCM (NePCM), composed of paraffin wax embedded with copper (Cu) nanoparticles. The NePCM is confined within a trapezoidal cavity, with the base serving as the heat source. Four different cavity heights were analyzed: cases 1, 2, 3, and 4 with the heights D of 24 mm, 18 mm, 15 mm, and 13.5 mm, respectively. The finite element method was employed to solve the governing equations. The influence of two hot base temperatures (333.15 K and 338.15 K) and Cu nanoparticle volume fractions ranging from 0% to 6% was examined. The results show that incorporating Cu nanoparticles at 6 vol% (volume fraction) enhanced thermal conductivity and reduced melting time by 10.71%. Increasing the base temperature to 338.15 K accelerated melting by 65.55%. Among all configurations, case 4 exhibited the best performance, reducing melting duration by 15.12% compared to case 1.